Earnings dynamics and firm-level shocks - Benjamin Friedrich; Lisa Laun; Costas Meghir; Luigi Pistaferri (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2019)
We use matched employer-employee data from Sweden to study the role of the firm in affecting the stochastic properties of wages. Our model accounts for endogenous participation and mobility decisions. We find that firm-specific permanent productivity shocks transmit to individual wages, but the effect is mostly concentrated among the high-skilled workers; firm-specific temporary shocks mostly affect the low-skilled. The updates to worker-firm specific match effects over the life of a firm-worker relationship are small. Substantial growth in earnings variance over the life cycle for high-skilled workers is driven by firms accounting for 44% of cross-sectional variance by age 55.
Keywords: H51; H55; I18; J26; 330; Income process; Wage dynamics; Firm dynamics